PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA NEARPOD TERHADAP HASIL BELAJAR SISWA PADA ELEMEN KOMUNIKASI DI TEMPAT KERJA KELAS XI MPLB DI SMKN 1 MEDAN T.A. 2025/2026 - Natasya, Melinda; Sri Mutmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine and analyze the effect of the Nearpod-assisted Problem-Based Learning (PBL) model on students’ learning outcomes in the Office Guest Handling in Indonesian Language learning achievement of Grade XI MPLB students at SMKN 1 Medan in the 2025/2026 Academic Year. This research employed a quantitative approach using an experimental method with a quasi-experimental design in the form of a nonequivalent control group design. The sample was selected through purposive sampling, with Class XI MPLB 3 as the experimental group receiving Nearpod-assisted PBL and Class XI MPLB 1 as the control group receiving PBL without Nearpod. Data were collected using a multiple-choice learning outcomes test that met the criteria of validity, reliability, item difficulty, and discrimination index. Data analysis included the calculation of means and standard deviations, as well as normality, homogeneity, and Independent Sample T-Test analyses using SPSS version 25. The results showed that the mean pre-test and post-test scores of the control group were 67.88 and 80.45, respectively, while those of the experimental group were 74.43 and 85.43. The normality test indicated that the pre-test and post-test data in both groups were normally distributed, with significance values greater than 0.05. The homogeneity test showed that the data were homogeneous, with a significance value of 0.053 (> 0.05). The hypothesis test revealed a significance value (2-tailed) of 0.017 (< 0.05) and tcount > ttable (2.446 > 1.668). Therefore, the Nearpod-assisted Problem-Based Learning model had a positive and significant effect on students’ learning outcomes.